The Current Role of Remote Human Services Internships: A Follow-Up Study - Nicole Kras; Jennifer Keenan (Journal of Human Services)
Health and safety concerns and universal restrictions throughout the COVID-19 pandemic lead to an increase in remote internships in the human services field. This was the first experience for many human services graduate and undergraduate programs with this type of internship placement. An initial study conducted during the summer of 2021 found that participants had mixed feelings about remote internships and were unsure of its role in the future. This study investigates the attitudes of faculty, students, and human services professionals on remote internships and their role in the human services field approximately a year and half after the initial study and three years after lockdown measures were put in place in March 2020. Flexibility and cost-effectiveness continue to be the most frequently noted strengths of remote internships, making the argument as a more equitable option for students, while the biggest challenge remained the lack of in-person interactions both with clients and colleagues. Findings indicate that human services programs are continuing to offer remote internships and most participants believe that they will play a significant role in the future. This study adds to the discussion about the role remote internships will play in a post-pandemic society, a society that is currently experiencing major transitions in the fields of human services and in higher education. As students call for more flexible learning modalities and human services education programs assess remote and hybrid internships models as viable options for their students, there is also a critical need to identify best practices in the implementation and support of these types of learning experiences.